Effect of wind energy development on breeding duck densities in the Prairie Pothole Region1. Issue 3 (24th December 2012) - Loesch, Charles R.; Walker, Johann A.; Reynolds, Ronald E.; Gleason, Jeffrey S.; Niemuth, Neal D.; Stephens, Scott E.; Erickson, Michael A.
Abstract: Industrial wind energy production is a relatively new phenomenon in the Prairie Pothole Region and given the predicted future development, it has the potential to affect large land areas. The effects of wind energy development on breeding duck pair use of wetlands in proximity to wind turbines were unknown. During springs 2008–2010, we conducted surveys of breeding duck pairs for 5 species of dabbling ducks in 2 wind energy production sites (wind) and 2 paired reference sites (reference) without wind energy development located in the Missouri Coteau of North Dakota and South Dakota, USA. We conducted 10, 338 wetland visits and observed 15, 760 breeding duck pairs. Estimated densities of duck pairs on wetlands in wind sites were lower for 26 of 30 site, species, and year combinations and of these 16 had 95% credible intervals that did not overlap zero and resulted in a 4–56% reduction in breeding pairs. The negative median displacement observed in this study (21%) may influence the prioritization of grassland and wetland resources for conservation when existing decision support tools based on breeding‐pair density are used. However, for the 2 wind study sites, priority was not reduced. We were unable to directly assess the potential for cumulative impacts and recommend long‐term, large‐scale waterfowl studies to reduce the uncertainty related to effects of broad‐scale wind energy development on both abundance and demographic rates of breeding duck populations. In addition, continued dialogue between waterfowl conservation groups and wind energy developers is necessary to develop conservation strategies to mitigate potential negative effects of wind energy development on duck populations. Published 2012. This article is a U.S. Government work and is in the public domain in the USA.